Rancang Bangun Ransel Skateboard Listrik dengan Motor DC Brushless - Tianur Tianur (Jurnal Elektro dan Mesin Terapan, 2020)
Electric Skateboard Backpack is a means of transportation used to facilitate moving from one place to another. This means of transportation is designed as a means of transportation that is easy to carry, does not require large space for storage, esthesis and environmentally friendly. This Electric Skateboard Backpack is designed with a simple frame which consists of a Skateboard storage area and an easily foldable frame system that uses its users when carrying and storing it. This Electric Skateboard Backpack uses a brushless DC Motor drive system for the hub type because it is efficient, environmentally friendly and suitable for electric vehicle. This Electric Skateboard Backpack has a length dimension of 800 mm and a height of 700 mm and has a frame system that can be folded thereby reducing the dimensions of its length. Based on testing this Electric Skateboard Backpack can carry loads that can be transported weighing 80 kg and the use time of this tool can reach 50 minutes of normal use. The speed that can be achieved is 7,2 km / hr in no-load conditions on the rough surface.